Linear Low-Intensity Extracorporeal Shockwave Therapy as a Method for Penile Rehabilitation in Erectile Dysfunction Patients after Radical Prostatectomy: A Randomized, Single-Blinded, Sham-Controlled Clinical Trial - Motil, Igor; Macik, Daniel; Sramkova, Katerina; Jarkovsky, Jiri; Sramkova, Tatjana (Urologia internationalis, 2022)
INTRODUCTION: The objective of this study was to investigate the effect and feasibility of linear low-intensity extracorporeal shockwave therapy (LI-LiESWT) as a penile rehabilitation method for erectile dysfunction (ED) after bilateral nerve-sparing (NS) radical prostatectomy (RP). METHODS: Patients who had undergone bilateral NS RP (either radical retropubic prostatectomy or robot-assisted laparoscopic RP), 3 or more months prior to the study, and who had no ED preoperatively and were suffering from mild to severe postoperative ED were included in the study. Four treatments were given over a 4-week period, using the PiezoWave2 device with a linear shockwave applicator and the linear shockwave tissue coverage (LSTC-ED®) technique. If the improvement in erectile function was still considered insufficient (less than an IIEF-5 score of 22-25) at 2 months after the start of LI-LiESWT, penile rehabilitation was supplemented by pharmacological penile rehabilitation. The final effect of treatment was evaluated after 12 months. The main outcome measure was changes in the five-item International Index of Erectile Function (IIEF-5) score. RESULTS: Between September 2019 and September 2020, a total of 40 patients were included in the study and randomly divided into 2 groups: treatment group and sham group. Eight patients were excluded from the study and were not evaluated due to other conditions which required additional treatment (COVID-19 disease, postoperative incontinence, urethral stricture, and ischemic stroke). Thirty-two patients were included in the final analysis: 16 in the control group and 16 in the intervention group. At 6 months from the end of treatment, patients in both the treatment and the sham group achieved physiological IIEF-5 values, and the beneficial effect persisted for 12 months after the end of treatment. CONCLUSIONS: LI-LiESWT using the LSTC-ED® technique is a suitable and safe method for penile rehabilitation in patients with ED after bilateral NS RP, not only because of the vasculogenic effect of LI-LiESWT but also because of its neuroprotective and/or regenerative effects.
Keywords: prostatektomie; Extracorporeal Shockwave Therapy; erektilní dysfunkce; COVID-19; Penile Erection; lidé; Erectile Dysfunction; výsledek terapie; Humans; Male; mužské pohlaví; Treatment Outcome; léčba mimotělní rázovou vlnou; Prostatectomy; erekce penisu